Access to medication in Mexico: financing and equity - Molina Salazar, Raúl Enrique; Díaz Pedroza, Jesús; Zuniga Trejo, Carmen; Saucedo Acosta, Edgar J. (Horizonte Sanitario, 2016)
Abstract: This paper presents some characteristics of the financing and access to medication in Mexico. It also shows the level of prices and costs of diabetes treatment. This study is based on the national survey about the income and expense of hoseholds from 1998 and 2010. The poorest households without social security, have an expense in medication relatively higher than the rest of the population which seems to be unfair. The cost of diabetes treatment with drugs without patent is too high.